Greenhouses within the Agricultura 4.0 interface - Costa, Edilson; Martins, Murilo; Vendruscolo, Eduardo; Silva, Abimael; Zoz, Tiago; Binotti, Flávio; Witt, Travis; Seron, Cássio (Revista Ciência Agronômica, 2021)
Global technological advances can be applied to all production sectors to improve people’s daily lives, efficiently deliver information, and product safety. This study is a literature review of the use of the Agricultura 4.0 interface in greenhouses and the improvements that these technologies have made to the industry. For the agricultural sector, especially intensive plant production in protected environments, Agricultura 4.0 technologies are widely used to reduce human error and ensure high quality plant products. Mathematical modeling, computer software, electronic meters, robotics, intelligent real-time system decisions, and automatic activity control throughout the production cycle guarantees extreme production safety in protected cultivation systems and precision planting environments. The accuracy, precision, and performance of Agricultura 4.0 in greenhouses depends, as in others agricultural sectors, on improved communication between digital platforms as well as in stable Internet for machine programming and operation in the production systems.